2021
DOI: 10.3390/ijms22031292
|View full text |Cite
|
Sign up to set email alerts
|

Omics and CRISPR-Cas9 Approaches for Molecular Insight, Functional Gene Analysis, and Stress Tolerance Development in Crops

Abstract: Plants are regularly exposed to biotic and abiotic stresses that adversely affect agricultural production. Omics has gained momentum in the last two decades, fueled by statistical methodologies, computational capabilities, mass spectrometry, nucleic-acid sequencing, and peptide-sequencing platforms. Functional genomics—especially metabolomics, transcriptomics, and proteomics—have contributed substantially to plant molecular responses to stress. Recent progress in reverse and forward genetics approaches have me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…Moreover, it turned out that the beneficial effects of biochar amendments could be evaluated by measuring the parameters used for monitoring water shortage and nutrient deprivation stress [123]. In summary, biochar primarily improves the reliability of water and nutrient supply, which allows plants to grow efficiently, while the window of stress resistance remains narrow [125]. Additional recent research indicated that the positive effect of biochar is not restricted to the water and nutrient supply to plant roots, but extends to soil microorganisms, as well [121,126].…”
Section: Improving Soil Quality By the Addition Of Biocharmentioning
confidence: 99%
“…Moreover, it turned out that the beneficial effects of biochar amendments could be evaluated by measuring the parameters used for monitoring water shortage and nutrient deprivation stress [123]. In summary, biochar primarily improves the reliability of water and nutrient supply, which allows plants to grow efficiently, while the window of stress resistance remains narrow [125]. Additional recent research indicated that the positive effect of biochar is not restricted to the water and nutrient supply to plant roots, but extends to soil microorganisms, as well [121,126].…”
Section: Improving Soil Quality By the Addition Of Biocharmentioning
confidence: 99%
“…CRISPR/Cas9 has been used to modify any sequence and to bring any character to crops. Molecular breeders discovered many genes related to abiotic stress tolerance and engineered them into crops [180]. CRISPR/Cas9 generated slmapk3 protein gene mutants improved defense response to drought stress in tomatoes [181].…”
Section: Development Of Climate-smart Crops Using Crispr/cas9mentioning
confidence: 99%
“…These studies indicate that the CRISPR/Cas9 technique has enormous potential for developing climate-adapted crops. The above studies showed that Cas9 could alter genes to facilitate resistance against many abiotic stresses, e.g., drought, high temperatures, heavy metals, as well as nutrient deficiencies [180]. A list of climate-smart crops is shown in Table 6.…”
Section: Development Of Climate-smart Crops Using Crispr/cas9mentioning
confidence: 99%
“…The process of gene regulatory dynamism in various cellular, physiological and biochemical mechanisms in plants was altered by environmental factors. Therefore, to analyze the processes involved in this regulatory mechanism, several functional omics projects, have been initiated across the world in recent years [ 49 , 73 , 74 ]. Moreover, multiple omics and bioinformatics approaches have been used for developing crop plants that are tolerant to AbS through molecular breeding and genetic engineering and also through advancements and increasing knowledge in genetics, genomics, and molecular physiology [ 75 , 76 ].…”
Section: Bioinformatics and Functional Omics Approach To Explore The Abs Tolerance Mechanismmentioning
confidence: 99%